2016
DOI: 10.1371/journal.pone.0161960
|View full text |Cite
|
Sign up to set email alerts
|

Motor Skills and Exercise Capacity Are Associated with Objective Measures of Cognitive Functions and Academic Performance in Preadolescent Children

Abstract: ObjectiveTo investigate associations between motor skills, exercise capacity and cognitive functions, and evaluate how they correlate to academic performance in mathematics and reading comprehension using standardised, objective tests.MethodsThis cross-sectional study included 423 Danish children (age: 9.29±0.35 years, 209 girls). Fine and gross motor skills were evaluated in a visuomotor accuracy-tracking task, and a whole-body coordination task, respectively. Exercise capacity was estimated from the Yo-Yo in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
107
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 32 publications
4
107
1
10
Order By: Relevance
“…Currently, the majority of the performed studies have been concerned with linking cognitive functions (Hillman et al, 2005; Voss et al, 2011) and academic achievements (Castelli et al, 2007; Chaddock-Heyman et al, 2015) to cardiovascular fitness in cross-sectional designs. Recent cross-sectional studies have positively linked motor skills to cognitive and academic measures (Kantomaa et al, 2013; Lopes et al, 2013; Haapala et al, 2014; Geertsen et al, 2016) and recent reviews have stressed the importance of the qualitative characteristics of the performed physical activity as compared to the quantitative characteristics of the physical activity (Best, 2010; Pesce, 2012; Diamond, 2015). In general, however, less focus has been paid to the qualitative characteristics of physical activity, and the relation of these to cognitive functions and academic achievements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the majority of the performed studies have been concerned with linking cognitive functions (Hillman et al, 2005; Voss et al, 2011) and academic achievements (Castelli et al, 2007; Chaddock-Heyman et al, 2015) to cardiovascular fitness in cross-sectional designs. Recent cross-sectional studies have positively linked motor skills to cognitive and academic measures (Kantomaa et al, 2013; Lopes et al, 2013; Haapala et al, 2014; Geertsen et al, 2016) and recent reviews have stressed the importance of the qualitative characteristics of the performed physical activity as compared to the quantitative characteristics of the physical activity (Best, 2010; Pesce, 2012; Diamond, 2015). In general, however, less focus has been paid to the qualitative characteristics of physical activity, and the relation of these to cognitive functions and academic achievements.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no previous studies have investigated the effects of different qualitatively focused motor enriching interventions (fine vs. gross motor skill) on cognitive and academic performance in children. Recently published cross-sectional study have indeed indicated that different coordinative motor skills, including both gross and fine motor skills, are associated with objective measures of cognitive functions and academic achievement, including mathematical performance, in children (Kantomaa et al, 2013; Haapala et al, 2014; Geertsen et al, 2016). While these associations are intriguing, they are correlational in nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that exercise can improve academic performance in adolescents without disability 39 and psychosocial health in children with cerebral palsy. 40 It is hoped that promotion of physical activity in childhood can set the course for a healthy lifestyle that prevents or minimizes fatigue, pain, and depression experienced by adults with cerebral palsy and other childhood-onset disabilities.…”
Section: Preventionmentioning
confidence: 99%
“…In practice, considering the human movements, EF are based on the ability to plan the action before the realization and the ability to predict the potential effects of specific actions. These functions are essential for mental and physical health [9]; for academic success [11]; for cognitive or psychological development [12] and then for social appreciation [9]. Thus they need an earlier development process during childhood [9] [13] using stimulus for problem-solving experiences, planning of events and association of concepts [14].…”
Section: Introductionmentioning
confidence: 99%